Unexpected rate retardation in the formation of phthalic anhydride from N-Methylphthalamic Acid in acidic H2O-CH3CN medium - Ariffin, Azhar; Khan, M.N. (2005)
Kinetic study on the cleavage of N-methylphthalamic acid (NMPA) in mixed acidic aqueous-acetonitrile solvent reveals the formation of both phthalic anhydride (PAn) (through O-cyclization) and N-methylphthalimide (NMPT) (through N-cyclization). The formation of NMPT varies from similar to 20% to similar to 3% with the increase in the content of acetonitrile from 2 to 70% v/v. Pseudo first-order rate constants for the formation of PAn are more than 4-fold larger than those for the formation of NMPT at 2% v/v CH3CN in mixed aqueous solvents. Pseudo first-order rate constants for alkaline hydrolysis of NMPT reveal a nonlinear decrease with increase in the content of CH3CN in mixed aqueous solvents.